Book Reviews (The Muslim world, 2001)
Book reviewed in this article: Jihad, The Origin of Holy War in Islam. Cairo. 1001 Years of Islamic Art and Architecture. The Social Origins of Islam: Mind, Economy, Discourse Sufis and Anti-Sufis: the Defence, Rethinking and Rejection of Sufism in the Modern World.